2013
DOI: 10.1371/journal.pone.0080234
|View full text |Cite|
|
Sign up to set email alerts
|

Olfactory Performance Is Predicted by Individual Sex-Atypicality, but Not Sexual Orientation

Abstract: Many previous studies have reported robust sex differences in olfactory perception. However, both men and women can be expected to vary in the degree to which they exhibit olfactory performance considered typical of their own or the opposite sex. Sex-atypicality is often described in terms of childhood gender nonconformity, which, however, is not a perfect correlate of non-heterosexual orientation. Here we explored intrasexual variability in psychophysical olfactory performance in a sample of 156 individuals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
0
14
0
1
Order By: Relevance
“…At last 24 articles were included (see selection flowchart in Figure 1). The studies (16,19,20,28,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) included for each of the three groups are shown in Table 1. Table 1 showed the demographic characteristics of participants and measures used in odor identification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At last 24 articles were included (see selection flowchart in Figure 1). The studies (16,19,20,28,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) included for each of the three groups are shown in Table 1. Table 1 showed the demographic characteristics of participants and measures used in odor identification.…”
Section: Resultsmentioning
confidence: 99%
“…We also conducted a subdivision comparison between female and male in the age 16-35 (16,19,20,40,45,47,49,52) . However, compared to the age 18-50, the effect size was relatively small (Cohen's d=0.36, 95% CI: 0.18 to 0.54), though a significant difference (Z = 3.87, p=0.0001) was found that female outperformed male in odor identification.…”
Section: Demographic Characteristics and Measures Used In Odor Identimentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the intercept term is omitted from the final output of the CATreg procedure using SPSS, the wide applicability of the CATreg with optimal scaling technique is not in doubt, especially amongst scholars (see Černá & Poulová, 2012;Hussain, Castaldi, & Cholette, 2006;Kooij, 2007;Nováková, Valentová, & Havlíček, 2014;Xu, Capretz, & Ho, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…It was possible that MSM males perform better in olfactory tasks than heterosexual, thus the observed lack of difference in olfactory sensitivity. The recent literature shows however, that it is gender nonconformity and sex-atypicality rather than sexual orientation (Nováková et al 2013) that influence sexual orientation. However, to further address this issue, the multiple regression analysis was performed.…”
Section: Discussionmentioning
confidence: 99%